MODEL OF RISE OF MOVEMENT AT ST. PAUL CATHOLIC JUNIOR HIGH SCHOOL IN PALANGKA RAYA - Pelesia Novidat Kristenina; Wiratno Y Sigin (Jurusan Pendidikan Teknologi Dan Kejuruan, 2023)
Traffic jams that occur in junior high schools during school hours can be prevented if before determining thelocation of the school, the school or other responsible parties first estimate the traffic generation on land use byknowing the magnitude of the generation, the geometry of the road sections in the area can be planned. school.The aim of this research is to obtain a movement generation model at schools in Palangka Raya City, which it ishoped can be used to estimate the number of movements coming to the school in the future, so that it can beused to anticipate problems arising from travel generation. This research was conducted at St. Paul CatholicMiddle School, Palangka Raya. The research used is quantitative descriptive research using survey methods. Themovement generation model for St. Paul's Catholic Middle School, Palangka Raya, after analyzing the simplelinear regression equation, which is most representative is Y4 = -2380,417 + 4,250 of 0.203. Factors that have astrong influence on the generation of movement at St Paul's Catholic Middle School in Palangka Raya are thenumber of students (X4) and the number of teachers and school employees (X5).